Hypothyroidism in pregnancy current guidelines, prevalence, and implications for maternal and fetal health - Elhardalo, Sahr Abdelrahman (International Journal of Research in Medical Sciences, 2025)
Hypothyroidism during pregnancy is a common endocrine disorder that can drastically impact the mother and fetus in the process of development. The two types of hypothyroidism in pregnancy are distinguished as overt and subclinical, with the latter being more prevalent. Subclinical hypothyroidism (SCH) is commonly caused by autoimmune thyroid disorders and iodine deficiency. In iodine-sufficient areas, hypothyroidism is caused by Hashimoto’s thyroiditis, whereas, in iodine-deficient areas, hypothyroidism is primarily caused by iodine deficiency. Diagnosing hypothyroidism during pregnancy is often challenging because its symptoms often mimic those of normal pregnancy. During pregnancy, thyroid function undergoes significant alterations. The disruption of the normal functioning of the hypothalamic-pituitary-thyroid axis causes fluctuations in both thyroid stimulating hormone (TSH) and thyroxine (T4) levels. Elevated human chorionic gonadotropin (hCG) and estrogen levels trigger the thyroid gland to increase hormone production. If hypothyroidism is not managed properly throughout pregnancy, it could lead to preeclampsia and premature delivery and neurodevelopmental concerns in the baby. It is recommended to consider hypothyroidism screening for women with autoimmune conditions or an existing history of thyroid disease due to their increased risk. The main treatment for pregnant women with hypothyroidism is levothyroxine, whose dosage is regulated to meet the increased demand for thyroid hormones. Continuous monitoring of free T4 levels and TSH is crucial in maintaining hormonal balance. The present review explores the prevalence of hypothyroidism during pregnancy, physiological changes, maternal and fetal complications, and the evidence-based guidelines for the management. Following current recommendations and proper treatment minimizes the risks for the mother and the baby.